(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Citizenship is more than just a legal status; it is a gateway to political participation, social inclusion, and long-term security. However, globally, states regulate access to citizenship through rules that determine how long applicants must reside, how challenging the process is, and how decisions are made to conform with standards. Therefore, this review paper examines citizenship acquisition rules while also comparing liberal (free) democracies, including Canada, the United States, the United Kingdom, and selected European Union states. Most importantly, it asks three major questions: how long does citizenship take, how hard is it to obtain, and how fair are the processes in practice? Hence, drawing on legal theory, policy reports, and justice, the paper argues that while states have legal rights in regulating membership, prolong, complex, or unnecessary processes risk undermine fairness, equality, and the rule of law.